USING FIX-UP STRATEGY TO IMPROVE STUDENTS READING COMPREHENSION (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
Fix-Up Strategy is an approach used in learning to help students overcome difficulties or confusion in understanding the material being studied. This strategy aims to help students improve or "fix" their understanding when they feel unsure or confused about the information provided. The study aims to investigate whether the implementation of the fix-up approach can improve the reading comprehension skills of students attending SMA Negeri 7 Palu. This research utilizes a quasi-experimental design involving two distinct groups: the experimental group, which consists of 35 students, and the control group, comprising 36 individuals. The selection of participants follows a random cluster sampling method. Two assessments, including a preliminary evaluation and a follow-up examination, were administered to gather data. Subsequently, the collected data underwent analysis using paired difference testing, specifically employing the paired sample t-test. The findings of the study suggest that employing the fix-up strategy leads to enhanced reading comprehension among tenth-grade students at SMA Negeri 7 Palu. The results of the paired sample t-test support this observation, indicating a significant difference in academic performance between the pre-test and post-test (two-tailed, p = 0.000 < 0.05).